E-Learning Website Development at the Tulungagung Regency BNN Using the Laravel Framework with an Extreme Programming (XP) Approach - Ardana Halim Wiradhika; Fahrur Rozi; Taufiq Agung Cahyono (Universitas Mohammad Husni Thamrin, 2026)
Drug misuse in Indonesia continues to pose a significant and far-reaching challenge, influencing multiple sectors of society, including the Tulungagung region. The National Narcotics Agency (BNN) of Tulungagung encounters various obstacles in delivering traditional outreach programs, notably constraints in manpower and infrastructure, the extensive geographical scope, and limited public engagement. In response to these issues, this research focuses on designing and developing a web-based e-learning platform to provide organized and easily accessible education on the dangers of drug abuse. The system is built using the Laravel framework and adopts the Extreme Programming (XP) approach, involving iterative cycles of planning, designing, coding, and testing.The resulting platform incorporates several key features, including user administration, pre-assessment, instructional content delivery, post-assessment, remedial modules, learning progress monitoring, digital certification, and an administrative dashboard for system oversight. Findings from the study demonstrate that the application performs in accordance with the defined functional specifications and effectively facilitates a structured learning process. Therefore, this e-learning platform is anticipated to enhance the efficiency of P4GN educational initiatives while also broadening the scope of digital outreach efforts conducted by BNN Tulungagung.